2004
DOI: 10.1029/2002jc001339
|View full text |Cite
|
Sign up to set email alerts
|

Direct velocity measurements in the Subantarctic Front and over Campbell Plateau, southeast of New Zealand

Abstract: [1] Flow variability in the Subantarctic Front (SAF) and over the Campbell Plateau, southeast of New Zealand, is examined using data from a current meter mooring array along with conductivity-temperature-depth (CTD) and satellite altimetry data. These data are part of an ongoing study of ocean climate variability in the region. Contrasting flow regimes were found with very energetic and highly variable flows in the SAF flowing along the Subantarctic Slope and much weaker flows over the Campbell Plateau. Curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
53
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(67 citation statements)
references
References 14 publications
13
53
1
Order By: Relevance
“…This compares with about 14% in the depth-independent component both south of Tasmania (Phillips & Rintoul 2000) and on the Subantarctic Slope (Stanton & Morris 2004). Transport in the SAF through the gaps in Macquarie Ridge is 52 Sv (Rintoul et al 2014), similar to the 48 to 68 Sv found on the Subantarctic Slope (Stanton & Morris 2004).…”
Section: Antarctic Circumpolar Currentsupporting
confidence: 65%
“…This compares with about 14% in the depth-independent component both south of Tasmania (Phillips & Rintoul 2000) and on the Subantarctic Slope (Stanton & Morris 2004). Transport in the SAF through the gaps in Macquarie Ridge is 52 Sv (Rintoul et al 2014), similar to the 48 to 68 Sv found on the Subantarctic Slope (Stanton & Morris 2004).…”
Section: Antarctic Circumpolar Currentsupporting
confidence: 65%
“…The mean velocities from the Argo trajectories are similar to the mean velocities at 1000 m from the dynamic height of the three hydrographic sections using the bottom as the LNM. Current meters deployed on a mooring at 52:9 S for 7 months show mean velocities of 25 and 23 cm s 21 at 1500 and 500 m depth, respectively [Stanton and Morris, 2004; values from their Table 1 with speeds projected into the cross track direction], which bracket the mean values from the Argo trajectories at 1000 m.…”
Section: Mean Surface Velocities From Argo Datamentioning
confidence: 99%
“…The mean is shown in subsequent figures for a comparison of a mean derived from the LNM. Transport has been estimated using these hydrographic sections and altimeter data by Stanton and Morris [2004]. They use a ''canonical'' velocity section from a subset of the hydrography and weight the section by the altimeter surface flow to find a transport more representative of 8 years than the three hydrographic sections alone.…”
Section: Mdt From Repeat Hydrography and Altimetrymentioning
confidence: 99%
See 2 more Smart Citations